Culture Mediums and Buffer Effect on Screen-printed Carbon Electrodes for Continuous Voltammetric Monitoring of in vitro Cell Cultures Lactate Production. (2017) - Rosati, G.; Scaramuzza, M.; Rotilio, V.; Monaco, L.; Pasqualotto, E.; Campolo, F.; De Toni, A.; Reggiani, C.; Naro, F.; Paccagnella, A.
Abstract: In this work we characterize and explain the difficulties related to voltammetric measurements in DMEM (Dulbecco's Modified Eagle's Medium) on widespread, commercially available Dropsens carbon screen-printed electrodes. The DMEM effects on the electrodes' surface is investigated by EIS, before and after 75 CV cycles. HBRS (Hepes Buffered Ringer's Solution) is proposed as alternative cell medium, and validated for the voltammetric monitoring of cell culture lactate production.